2019
DOI: 10.1097/01.hs9.0000561768.53887.ff
|View full text |Cite
|
Sign up to set email alerts
|

S872 Carfilzomib Lenalidomide Dexamethasone (Krd) With or Without Transplantation in Newly Diagnosed Myeloma (Forte Trial): Efficacy According to Risk Status

Abstract: Background: ENKTL account for more than 20% of the peripheral T-cell lymphoma in Asia. Patients with r/r ENKTL have a poor prognosis after failing an L-asparaginase based regimen, and the median overall survival is less than 6 months. The overexpression of PD-L1 induced by EBV infection is a potential mechanism for ENKTL to avert immune surveillance, and recent studies of PD-1 antibodies in pts with r/r ENKTL have demonstrated potential efficacy. Sintilimab, a fully human anti-PD-1 monoclonal antibody, has a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
2
22
0
Order By: Relevance
“…Conversely, reaching MRD negativity at a sensitivity of 10 −5 -10 −6 seemed to overcome the inferior outcome observed in high-risk vs. standard-risk patients (48,58). However, it should be noted that high-risk patients require highly intensive regimens in order to achieve a proper level of MRD negativity (47,52,55).…”
Section: Mrd Results In the Clinical Setting: Relevant Questionsmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, reaching MRD negativity at a sensitivity of 10 −5 -10 −6 seemed to overcome the inferior outcome observed in high-risk vs. standard-risk patients (48,58). However, it should be noted that high-risk patients require highly intensive regimens in order to achieve a proper level of MRD negativity (47,52,55).…”
Section: Mrd Results In the Clinical Setting: Relevant Questionsmentioning
confidence: 94%
“…NTE NDMM in ≥PR after 6 VMP(52) or VTP(50) induction cycles MFC (10 −4 -10 −5 )Post-induction 30% 3-year PFS: 90% vs. NR Roussel et al(39) TE NDMM after 3 VRd + ASCT + 2 VRd cycles followed by lenalidomide maintenance ≥CR after ASCT (241) MFC (10 −4 -10 −5 ) +100 days after ASCT 64% 3-year TTP: 76% vs. 58%Ferrero et al (41) TE NDMM in ≥VGPR after ASCT (39) undergoing VTd consolidation ASO-PCR (10 −4 -10 −5 ) Longitudinal Post-ASCT: 23%, Post-consolidation: 57% 6-month post-consolidation: 72% Median PFS: 68 vs. 23 months Korthals et al (11) TE NDMM after 2-4 cycles of idarubicin-dexamethasone undergoing ASCT ASO-PCR (10 −4 -10 −5 ) Post-induction and post-ASCT (+3-6 months) Post-induction: 17% Post-ASCT: 21% NA Lahuerta et al (42) NDMM alive and with MRD data available at 9 months after treatment start (609) MFC (10 −4 -10 −5 ) 9 months after treatment start 43% Median PFS* 63 months vs. NA (11-29 months in the other response categories) Gu et al (43) TE NDMM (101) MFC (50 −4 -10 −5 ) Longitudinal Post-induction: 37% Post-ASCT: 66% 2-year post-ASCT: 78% Median TTP: NR vs. NR Korde et al…”
mentioning
confidence: 99%
“…Both approaches produce deep remissions, with a majority of patients achieving an MRD‐negative state. A recent update of this study reported a higher rate of early recurrence in the group treated with KRd only (ie, nontransplantation) (23% vs 12% in the group who underwent transplantation) . Although the results of this study are immature and PFS and OS data are forthcoming, this interim analysis suggests that even with highly active induction regimens that can achieve an MRD‐negative disease state in a majority of patients, the incorporation of autoHCT continues to provide benefit.…”
Section: Introductionmentioning
confidence: 78%
“…More recently, the larger phase 2 FORTE clinical trial evaluated the efficacy of the same treatment schedule. Among 158 patients, NDMM patients who received KRd induction-ASCT-KRd consolidation, the CR or better rate was 60%, and the MRD-negative rate by NGF was 58% 10 . In all these studies, KRd was administered as induction followed by HDM/ASCT and KRd consolidation.…”
Section: Dear Editormentioning
confidence: 99%